Encyclopedia of human relationships - Reis, Harry T.; Sprecher, Susan 1955- (Gale virtual reference library, 2009)
Offers an interdisciplinary view of all types of human associations. Provides a state-of-the-art review of the extensive theories, concepts, and empirical findings about human relationships.